LEAD, HYPERTENSION, AND CHRONIC RENAL FAILURE - Haq, Nadeem ul; Tabassum, Saiqa; Anjum, Rosheena; Fatima, Batool (Journal of Ayub Medical College Abbottabad, 2013)
Background: Chronic kidney disease (CKD), a condition frequently attributed to uncontrolled diabetes and hypertension, has become an economic and public health burden both globally and locally. The present study was designed to investigate the toxic effects of lead and hypertension (HTN) on chronic renal failure (CRF). Method: It was a cross-sectional, prospective study conducted in Jinnah Postgraduate Medical Centre, Karachi. A total of 150 adults aged >40 years were included, 50 were diagnosed patients of hypertension, 50 were diagnosed patients of hypertension with chronic renal failure, and 50 were normal healthy individuals. Levels of lead in blood samples of HTN and CRF patients were estimated besides the levels of HbA1c, glucose, urea, creatinine and antioxidant enzymes (SOD, catalase, NO, Gluthathione peroxidase) by using kit method. Results: Lead levels were higher in HTN and CRF patients compared to controls. Urea, creatine and creatinine clearance levels were high in patients of HTN with CRF. Glucose and HbA1c levels were higher in HTN, and HTN with CRF patients compared to controls. The activity of antioxidant enzymes was decreased in HTN, and HTN with CRF patients. Conclusion: Lead exposure with HTN can be a cause of CRF. Keywords: Lead, Hypertension, Diabetes, Renal failure, Antioxidant Enzymes